1996
DOI: 10.1074/jbc.271.3.1295
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Direct Interaction between p56 and the Cytoplasmic Domain of CD45 in Vitro

Abstract: p56lck is a potential in vivo substrate for the tyrosinespecific phosphatase, CD45. In this study, recombinant purified p56 lck was found to specifically associate with recombinant CD45 cytoplasmic domain protein, but not to the cytoplasmic domain of another related tyrosine phosphatase, receptor protein-tyrosine phosphatase ␣. Under equilibrium binding conditions, the binding was saturable and occurred at a 1:1 molar stoichiometry. A fusion protein containing only the amino-terminal region of p56 lck (residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 41 publications
2
30
1
Order By: Relevance
“…This is in contrast to the predominant interaction between p56 lck and CD45, which is unaffected by MCD and is therefore unlikely to be DRM dependent. This is consistent with previous reports showing that recombinant p56 lck can bind to recombinant cytoplasmic region of CD45 in vitro (33).…”
Section: Discussionsupporting
confidence: 83%
“…This is in contrast to the predominant interaction between p56 lck and CD45, which is unaffected by MCD and is therefore unlikely to be DRM dependent. This is consistent with previous reports showing that recombinant p56 lck can bind to recombinant cytoplasmic region of CD45 in vitro (33).…”
Section: Discussionsupporting
confidence: 83%
“…In part, this interaction is probably indirect, as a consequence of the capacity of p56 lck to associate with CD4 and CD8 through its unique region (42,56) and possibly with CD45 via its unique and SH2 domains (52). Nonetheless, our transient expression experiments in COS-1 cells, and those in HeLa cells reported by others (25), showed that an association between CD45-AP and Lck could take place in the absence of other lymphoid-specific components.…”
Section: Discussioncontrasting
confidence: 42%
“…Although the basis for this association was not determined, it was shown to happen in the absence of CD4 and CD8 expression (15). Further experiments with recombinant proteins suggested that this interaction was possibly direct, as a result of an association between the cytoplasmic portion of CD45 and the unique and SH2 domains of p56 lck (52). Nevertheless, recent analyses of CD45-AP-deficient Tcells suggested that the association between CD45 and Lck may be facilitated by CD45-AP, especially in TCR-stimulated cells (30).…”
Section: Association Of Cd45-ap With Lck Can Occur Independently Of Cmentioning
confidence: 99%
“…In fact, it has been shown that p56 lck co-immunoprecipitates with CD45 thus establishing a link between these two molecules [9]. Although we have no data on the effect of CD148 on p56 lck , no clear phosphorylation of substrates around 56 Kd was detected after CD148 stimulation.…”
Section: Resultsmentioning
confidence: 68%